Indirect Evaluation of Program Educational Objectives and Student Outcomes for Engineering Programs: A Case Study - Ghaly, S. M. A. (Engineering, Technology & Applied Science Research, 2020)
Outcome and objective assessment is a method for determining whether students and graduates have learned, have retained, and can apply what they have been taught. Assessment plans have to include a statement of educational objectives, measurements of attainment of the objectives, and use of the assessment results for continuous improvement. In this paper, the experience of the Electrical Engineering program at Al-Imam Mohammad Ibn Saud Islamic University is used as an example of how an indirect assessment method is established and implemented. Many surveys have been used and contributed to the numerical analysis for the indirect assessment of the program outcomes and achievements. The indirect assessment results indicate that the target levels are achieved for all the seven program outcomes and the three objectives that have been considered.